Castaño, Sergio Raúl (2018). Il potere costituente tra mito e realtà, Prefacio de Pietro Giuseppe Grasso. Milano. Giuffrè Francis Lefebvre. XIV+135 páginas. ISBN 9788828803607 - Herrera, Daniel Alejandro (2021)
Fil: Herrera, Daniel Alejandro. Pontificia Universidad Católica Argentina; Argentina